Therapeutic models in positive clinical interventions for reducing depressive symptoms in adults: a systematic review - Sánchez-Cisneros, Daniel; Rodríguez-Hernández, Gabriela; Juárez Lugo, Carlos Saúl; Orozco Vargas, Arturo Enrique; Flores-Pérez, Virginia (Interacciones, 2024)
Background: Depression is currently one of the most common mental disorders worldwide. Although there are valuable and effective psychotherapeutic models for its treatment, most focus on reducing symptoms and illness. In contrast, the Positive Psychology approach promotes well-being by developing and implementing strategies, called Positive Clinical Interventions (PCIs) that aim to enhance the development and satisfaction of individuals to promote health, quality of life, and excellence. Methods: This review aimed to synthesize the available evidence on the effectiveness of PCIs according to the type and therapeutic model implemented to increase well-being and reduce depressive symptoms in adults, as well as to identify their value and balance between innovation and effectiveness. We searched PubMed, PsycINFO and SCOPUS, followed the PRISMA guidelines and assessed the methodological quality of the studies. Our review has been registered in PROSPERO (CRD42024551678). Results: The methodological quality of the studies was assessed using the Effective Public Health Practice Project (EPHPP), which allowed six studies out of 178 to be included in the systematic review. Second and third-generation treatment models were identified. All studies reported an improvement in depressive symptoms and an increase in well-being immediately after the intervention and up to six months later. Conclusions: According to the results, PCIs are effective, but studies with more rigorous protocols and methods are needed to avoid bias.